Medium and low temperature porous wave-absorbing iron-based composite ceramic and preparation method thereof
By developing a method for preparing porous, low-temperature absorbing iron-based composite ceramics, the problems of high-temperature performance degradation and high processing costs of iron-based absorbing ceramics have been solved. This method achieves wideband, high-efficiency absorption and lightweight design, making it suitable for military stealth and electromagnetic shielding applications.
Patent Information
- Application Number
- CN202510932240.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-10-21
AI Technical Summary
The high-temperature sintering of existing iron-based microwave absorbing ceramics leads to performance degradation, crude structural control, simple loss mechanism, and high process cost, making it difficult to achieve broadband absorption and lightweight design.
A method for preparing medium-low temperature porous microwave absorbing iron-based composite ceramics was adopted. By introducing low-temperature glass powder and biodegradable pore-forming agent and combining it with cryogenic molding technology, a gradient porous structure was constructed to achieve magnetic-dielectric synergistic loss and reduce the sintering temperature to below 750℃.
It achieves wideband and high-efficiency wave absorption performance, lightweight and high stability, reduces material density and cost, and avoids the generation of toxic byproducts.
Smart Images

Figure CN120817779A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functional ceramic materials and electromagnetic wave absorption technology, and in particular to a medium- and low-temperature porous wave-absorbing ceramic with an iron-based composite as a core wave-absorbing component and a preparation method thereof. Background Art
[0002] Absorbing materials have important application value in the fields of stealth technology, electromagnetic compatibility and electronic equipment protection. Iron-based compounds (such as ferrite, iron-cobalt alloy, etc.) have become one of the core components of absorbing materials due to their advantages such as high magnetic permeability and low cost. However, the preparation and application of traditional iron-based absorbing ceramics still have the following technical bottlenecks: Existing iron-based absorbing ceramics mostly rely on high-temperature solid-phase reactions (>1300°C) to achieve densification, and need to be sintered at 1350°C, which causes the iron-based absorber (such as Fe3O4) to coarsen grains or even oxidative decomposition (generating Fe2O3), and the magnetic loss performance drops by more than 30%. High-temperature sintering will also increase the material density (>3.5g / cm 3 ), which contradicts the need for lightweighting. Existing iron-based absorbers are primarily magnetically lossy, lacking dielectric loss synergy. The imaginary part of the dielectric constant (ε") of a single Fe3O4 ceramic is only 0.5-1.2 (2-18 GHz), making broadband absorption difficult. Carbon fiber is typically added to enhance dielectric loss, but high-temperature sintering causes oxidation and fracture of the carbon fibers, increasing the material's resistivity by two orders of magnitude.
[0003] In summary, the current preparation technology of iron-based absorbing ceramics faces a series of problems: "high-temperature performance degradation - extensive structural control - single loss mechanism - high process cost". Summary of the Invention
[0004] In response to the problems of existing iron-based absorbing ceramics such as deteriorated high-temperature sintering performance, difficult porous structure control, single loss mechanism and high process cost, the present invention proposes a medium- and low-temperature porous absorbing iron-based composite ceramic and its preparation method.
[0005] The present invention provides a medium-low temperature porous wave-absorbing iron-based composite ceramic, characterized by comprising the following raw materials in percentage by weight:
[0006] Wave absorbing functional phase 10-50wt%, ceramic matrix 20-40wt%, pore forming agent 5-15wt%,
[0007] Dielectric loss phase 5-10wt%, stearic acid 0.5-1wt%, silane coupling agent 0.2-0.5wt%,
[0008] 30-34.5wt% of the binder phase; wherein:
[0009] The absorbing functional phase is a magnetic loss absorber with carbonyl iron powder or Fe-Co alloy as the core; the dielectric loss phase is silicon carbide nanowires, chopped carbon fibers or reduced graphene oxide; the ceramic matrix is Al2O3, SiO2 or calcium silicate; the bonding phase is low-temperature glass powder, which is a B2O3-Na2O-K2O-SiO2 system with a softening point of 600-750°C; and the pore-forming agent is calcium carbonate, starch and rice husk ash.
[0010] The present invention also provides a method for preparing the medium- and low-temperature porous wave-absorbing iron-based composite ceramic, comprising the following steps:
[0011] Step 1: Raw material processing
[0012] The microwave-absorbing functional phase is placed in a ball milling jar protected by argon, stearic acid is added as a dispersant, and the microwave-absorbing functional phase coated with antioxidant is obtained after ball milling and dispersion.
[0013] The dielectric loss phase is added to anhydrous ethanol, and after ultrasonic treatment, a silane coupling agent is added and stirred to form a uniform dielectric loss phase suspension;
[0014] Step 2: Mix in steps
[0015] The treated absorbing functional phase is mixed with a ceramic matrix and a binder phase, and the mixture is dispersed by ball milling to obtain a ceramic matrix mixed powder;
[0016] Mixing the dielectric loss phase suspension with the ceramic matrix mixed powder and the pore-forming agent, and stirring to form a uniform slurry;
[0017] Step 3: Freeze injection molding of porous structure
[0018] The slurry is injected into a mold at a sub-zero temperature, and the temperature is further reduced and kept warm, so that an ice crystal template is formed inside the slurry; the pre-frozen slurry is taken out and vacuum freeze-dried to remove the ice crystals and part of the solvent to obtain a green body with a closed-cell structure;
[0019] Step 4: Two-stage low-temperature sintering
[0020] The green body is placed in an electric furnace, and the temperature is gradually raised to 400-500° C. for pre-sintering, and the temperature is kept to decompose the pore-forming agent to form a stable skeleton;
[0021] Continue to gradually raise the temperature to 600-750℃ for main sintering, and then keep the temperature to melt the low-temperature glass phase to obtain porous ceramics;
[0022] Step 5: Processing and surface modification
[0023] The sintered porous ceramic is ground and polished with a water-based organic solution, and then heat-treated in a nitrogen mixed gas at a temperature of 500-550° C. to obtain the medium- and low-temperature porous wave-absorbing iron-based composite ceramic.
[0024] Preferably, in step 1, the absorbing functional phase uses: carbonyl iron powder with a particle size of 1-20 μm, Fe-Co alloy powder with a particle size of 2-20 μm, and Fe:Co = 7:3; the ball milling time is 2-4 hours, and the rotation speed is 400 r / min; the dielectric loss phase uses: silicon carbide nanowires with a diameter of 50-200 nm and an aspect ratio > 50 or chopped carbon fibers with a length of 50-200 μm; the ultrasonic treatment is 20 to 40 minutes, and the power is 500 W; the stirring is 0.5 to 2.5 hours.
[0025] Preferably, in step 2, the particle size of the ceramic matrix is 0.5-50 μm; the low-temperature glass powder is a B2O3-Na2O-K2O-SiO2 system with a softening point of 600-750°C; the ball milling is performed for 3 to 6 hours at a rotation speed of 400 r / min; the pore-forming agent is calcium carbonate with a particle size of 0.5 to 10 μm; and the starch and rice husk ash microspheres have a particle size of 0.05-1 mm.
[0026] Preferably, in step 3, the mold pre-cooling temperature is -10 to -15°C; the temperature is further lowered to -15 to -25°C, and the heat preservation is performed for 5 to 10 hours; the vacuum freeze drying is performed for 24 to 48 hours, the temperature is -40 to -55°C, and the pressure is ≤60Pa.
[0027] Preferably, in step 4, the temperature rise curve of the pre-sintering is 1-2.5° C. / min, and the holding time is 1.5-3 hours; the temperature rise curve of the main sintering is 2-3° C. / min, and the holding time is 0.5-1.5 hours.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) Optimize low-temperature sintering process to protect the activity of magnetic loss phase
[0030] Solve the problem of high-temperature oxidation: The sintering temperature of traditional iron-based absorbing materials is high, which leads to oxidation and decomposition of iron powder or ferrite (such as Fe3O4→Fe2O3), and the magnetic loss performance decreases.
[0031] Medium and low temperature protection mechanism: The iron-based composite ceramic of the present invention reduces the sintering temperature to below 750°C by introducing a B-Na / K-Si-O low-temperature glass phase (softening point 600-750°C), thereby protecting the activity of the magnetic loss phase.
[0032] (2) Gradient porous structure design to achieve broadband and efficient wave absorption
[0033] Using the freeze injection molding method, a porous iron-based composite ceramic with a closed porosity of ≥60% and a pore size gradient (100nm-3mm) is constructed, effectively balancing lightweight (body density 0.1-0.8g / cm 3 ) and mechanical strength (compressive strength ≥ 2MPa). The gradient pore structure, through a multiple reflection-scattering mechanism, enables the iron-based composite ceramic to have an effective absorption band (RL ≤ -10dB) covering 8-18GHz, with a peak loss of -25dB (at 15GHz).
[0034] (3) Enhanced magnetic-dielectric synergistic loss, breaking through the limitations of a single mechanism
[0035] With Fe-Co alloy or carbonyl iron powder (5-30wt%) as the core magnetic loss phase (wave absorbing functional phase), the imaginary part of the magnetic permeability (μ") is improved, and the low-frequency wave absorption performance is significantly enhanced. Dielectric loss enhancement: SiC or chopped carbon fiber (5-20wt%) is introduced to improve the imaginary part of the dielectric constant (ε") and expand the high-frequency absorption capacity through interface polarization.
[0036] (4) Green process and short process design
[0037] Using starch or rice husk ash microspheres as biodegradable pore-forming agents avoids the high-temperature decomposition of traditional pore-forming agents (such as polystyrene) that produces toxic benzene gases. Single-step sintering (650-750°C) significantly reduces VOC emissions compared to traditional multi-step impregnation processes.
[0038] (5) Improved mechanical properties and stability
[0039] After melting, the low-temperature glass phase forms a chemical bond with the iron-based absorber, increasing interfacial bonding strength, flexural strength, and enhanced interfacial bonding. The porous structure reduces thermal stress concentration, and the material undergoes 10 thermal shock cycles at 500°C without cracking. Its low thermal conductivity makes it suitable for high-temperature stealth applications.
[0040] (6) Application scenario expansion and cost advantages
[0041] Bulk density as low as 0.05g / cm 3 , suitable for weight-sensitive stealth equipment such as aircraft and drones, as well as low-altitude aircraft. Replacing traditional silicon carbide-based materials with low-cost ceramic matrices such as calcium silicate and Al2O3 reduces overall costs.
[0042] The present invention solves the problems of traditional iron-based absorbing ceramics such as degraded high-temperature performance, narrow absorption bandwidth, and low mechanical strength through low-temperature sintering process optimization, gradient porous structure design, enhanced magnetic-dielectric synergistic loss, and green short-process technology. It combines the advantages of broadband high-efficiency absorption, lightweight, high stability, and low cost, and is suitable for military stealth, electromagnetic shielding, and high-temperature electronic protection. The present invention specifically proposes: a medium-low temperature sintering process: by introducing a low-temperature sintering aid (such as a B2O3-SiO2 glass phase), the sintering temperature is reduced to below 750°C, protecting the microstructure of the iron-based absorber and meeting the lightweight requirement; magnetic-dielectric synergistic loss: using ferrite as the magnetic loss phase, carbon fiber and silicon carbide as the dielectric loss phase, the broadband absorption performance is improved through the interfacial polarization effect; green and low-cost preparation: using water-based slurry molding and degradable pore-forming agents (such as starch and rice husk ash) to avoid the formation of toxic byproducts. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a flow chart for preparing the low-temperature porous wave-absorbing iron-based composite ceramic of the present invention;
[0044] Figure 2 This is a photo of the medium- and low-temperature porous wave-absorbing iron-based composite ceramic according to Example 1 of the present invention;
[0045] Figure 3 This is a microscopic image of the medium- and low-temperature porous wave-absorbing iron-based composite ceramic according to Example 2 of the present invention;
[0046] Figure 4 This is the wave absorbing performance curve of the medium and low temperature porous wave absorbing iron-based composite ceramic of Example 3 of the present invention. DETAILED DESCRIPTION
[0047] The technical solutions of the present invention are described clearly and completely below with reference to the embodiments and drawings. The described embodiments are only a part of the embodiments of the present invention and are not intended to limit the present invention.
[0048] The present invention provides a medium-low temperature porous wave-absorbing iron-based composite ceramic, which is prepared from the following raw materials in percentage by weight:
[0049] Wave absorbing functional phase 10-50wt%, ceramic matrix 20-40wt%, pore forming agent 5-15wt%,
[0050] Dielectric loss phase 5-10wt%, stearic acid 0.5-1wt%, silane coupling agent 0.2-0.5wt%,
[0051] Binder phase 30-34.5wt%.
[0052] The absorbing functional phase (magnetic loss phase) is a magnetic loss absorber with a core of carbonyl iron powder or an iron-based alloy (Fe-Co). The ceramic matrix is Al2O3, SiO2, or calcium silicate. The binder phase is low-temperature glass powder. The pore-forming agents are calcium carbonate, starch, and rice husk ash. The dielectric loss phase is silicon carbide nanowires (SiC NWs), chopped carbon fibers, or reduced graphene oxide (rGO).
[0053] In order to obtain the ceramic phase composition and structure, the present invention provides a method for preparing the medium and low temperature porous wave absorbing iron-based composite ceramic, comprising the following steps (please refer to Figure 1 ):
[0054] 1. Raw material pretreatment
[0055] S1. Pretreatment of the absorbing function phase (magnetic loss phase)
[0056] Carbonyl iron powder with a particle size of 1-20 μm or Fe-Co alloy powder with a particle size of 2-20 μm, Fe:Co=7:3, is placed in a ball mill protected by argon, stearic acid is added as a dispersant, and ball milled for 2-4 hours at a speed of 400 r / min to obtain an antioxidant-coated Magnetic loss phase ;
[0057] S2, dielectric loss phase dispersion
[0058] Silicon carbide nanowires (SiC NWs) with a diameter of 50-200 nm and an aspect ratio of >50 or chopped carbon fibers with a length of 50-200 μm are added to anhydrous ethanol and ultrasonically treated for 20-40 minutes at a power of 500 W. A silane coupling agent (KH550) is then added and stirred for 0.5-2.5 hours to form a uniform dielectric loss phase suspension.
[0059] 2. Step-by-step mixing
[0060] S3, the pretreated magnetic loss phase, the ceramic matrix powder with a particle size of 0.5-50 μm, and the low-temperature glass powder are mixed in a B2O3-Na2O-K2O-SiO2 system with a softening point of 600-750°C according to the amount ratio of the raw materials, and ball milled for 3-6 hours at a speed of 400 r / min to obtain a ceramic matrix mixed powder;
[0061] S4, mixing the dielectric loss phase suspension with the ceramic matrix powder, pore-forming agent The mixture is mixed and stirred to form a uniform slurry, wherein the particle size of the calcium carbonate as a pore-forming agent is 0.5-10 μm; and the particle size of the starch and rice husk ash microspheres is 0.05-1 mm.
[0062] 3. Porous structure forming
[0063] S5, Freeze Injection Molding (Applicable to Closed Cell Structure)
[0064] The slurry is injected into a pre-cooled metal or plastic mold, the mold pre-cooling temperature is -10 to -15°C, and then cooled to -15 to -25°C and kept warm for 5 to 10 hours to form an ice crystal template inside the slurry; the pre-frozen slurry is taken out and vacuum freeze-dried for 24 to 48 hours (temperature is -40 to -55°C, pressure is ≤60Pa) to remove ice crystals and part of the solvent to form a green body with a closed-cell structure.
[0065] 4. Two-stage low-temperature sintering
[0066] S6, pre-sintering stage (degreasing and pore structure fixing)
[0067] The green body is placed in an electric furnace, heated to 400-500° C. at a rate of 1-2.5° C. / min, and kept warm for 1.5-3 hours to decompose the pore-forming agent and form a stable skeleton.
[0068] S7, main sintering stage (ceramic densification and glass phase melting)
[0069] The temperature is raised to 600-750°C (heating rate 2-3°C / min) and kept at this temperature for 0.5-1.5 hours to melt the low-temperature glass phase, achieve matrix densification, and obtain a certain strength to obtain porous ceramics.
[0070] 5. Processing and surface modification
[0071] S8. Grinding and polishing the sintered porous ceramic with a water-based organic solution to form it into a certain shape and size, and then heat-treating it under a nitrogen mixed gas (500-550° C.) to form a graphitized carbon layer on its surface to obtain the medium- and low-temperature porous absorbing iron-based composite ceramic.
[0072] According to the ratio of the above-mentioned medium-low temperature porous wave-absorbing iron-based composite ceramic raw materials, five embodiments 1-5 were prepared, as shown in Table 1.
[0073] Table 1
[0074]
[0075] The medium- and low-temperature porous wave-absorbing iron-based composite ceramics of the present invention are prepared according to the raw material dosage ratios of the five examples shown in Table 1.
[0076] Example 1
[0077] S1, pretreatment of the magnetic loss phase (wave absorbing functional item): carbonyl iron powder (31 wt%) was placed in an argon-protected ball mill, 0.4 wt% stearic acid was added as a dispersant, and ball milling was performed for 2 hours (rotation speed 400 r / min) to obtain an antioxidant-coated magnetic loss phase.
[0078] S2, dielectric loss phase dispersion, short carbon fiber (1wt%) + SiC (10wt%) was added to anhydrous ethanol and ultrasonically treated for 30 minutes (power 500W), and then 0.1wt% silane coupling agent (KH550) was added and stirred for 1.2 hours to form a uniform suspension.
[0079] S3, mixing the pretreated magnetic loss phase, ceramic matrix powder (SiO2 (10 wt%) + calcium silicate (5 wt%)), and low-temperature glass powder (B-Na-Si-O glass (34.5 wt%)) in proportion, and ball milling for 4.5 hours (rotation speed 400 r / min) to obtain matrix mixed powder;
[0080] S4, mixing the dielectric loss phase suspension with the matrix mixed powder and the pore-forming agent (calcium carbonate (7 wt %) + starch microspheres (3.4 wt %)), and stirring to form a uniform slurry.
[0081] S5, freeze injection molding, the slurry is injected into a pre-cooled metal mold (-15℃), then cooled to -19℃ and kept warm for 6 hours to form an ice crystal template inside the slurry; then vacuum freeze drying is carried out for more than 24 hours (temperature, -45℃, pressure 60Pa) to remove ice crystals and part of the solvent to form a green body with a closed-pore structure.
[0082] S6, pre-sintering stage (debinding and pore structure fixation), the green body is placed in an electric furnace, heated to 500 ° C at 1.5 ° C / min, and kept at this temperature for 2 hours to decompose the pore-forming agent and binder to form a stable skeleton.
[0083] S7, the main sintering stage (ceramic densification and glass phase melting), the temperature is raised to 660 ° C (heating rate 2.5 ° C / min), and kept at this temperature for 0.5 hours to melt the low-temperature glass phase and achieve matrix densification with a certain strength.
[0084] S8, grinding and polishing the sintered porous ceramics with a water-based organic solution to form a certain shape and size, and then heat-treating them (550°C) under a nitrogen mixed gas to form a graphitized carbon layer on the surface to obtain a medium- and low-temperature porous absorbing iron-based composite ceramic.
[0085] Example 2
[0086] S1, magnetic loss phase pretreatment, carbonyl iron powder (35wt%) was placed in an argon-protected ball mill, 0.4wt% stearic acid was added as a dispersant, and ball milling was performed for 3 hours (rotation speed 400r / min) to obtain an antioxidant-coated magnetic loss phase.
[0087] S2, dielectric loss phase dispersion, short carbon fiber (2wt%) + SiC (8wt%) was added to anhydrous ethanol and ultrasonically treated for 40 minutes (power 500W), and then 0.2wt% of silane coupling agent (KH550) was added and stirred for 1 hour to form a uniform suspension.
[0088] S3, mixing the pretreated magnetic loss phase, ceramic matrix powder (Al2O3 (3 wt%) + SiO2 (11 wt%)), and low-temperature glass powder (B-Na-Si-O glass (30 wt%)) in proportion, and ball milling for 4 hours (rotation speed 400 r / min) to obtain matrix mixed powder;
[0089] S4, mixing the dielectric loss phase suspension with the matrix mixed powder and the pore-forming agent (calcium carbonate (5 wt%) + rice husk ash microspheres (3 wt%)), and stirring to form a uniform slurry.
[0090] S5, freeze injection molding, the slurry is injected into a pre-cooled metal mold (-10℃), then cooled to -16℃ and kept warm for 6 hours to form an ice crystal template inside the slurry; then vacuum freeze drying is carried out for more than 27 hours (temperature, -48℃, pressure 55Pa) to remove ice crystals and part of the solvent to form a green body with a closed-pore structure.
[0091] S6, pre-sintering stage (debinding and pore structure fixation), the green body is placed in an electric furnace, heated to 500 ° C at 1.8 ° C / min, and kept at this temperature for 1.5 hours to decompose the pore-forming agent and binder to form a stable skeleton.
[0092] S7, the main sintering stage (ceramic densification and glass phase melting), the temperature is raised to 680 ° C (heating rate 2.3 ° C / min), and kept at this temperature for 0.6 hours to melt the low-temperature glass phase and achieve matrix densification with a certain strength.
[0093] S8, grinding and polishing the sintered porous ceramics with a water-based organic solution to form a certain shape and size, and then heat-treating (530°C) under a nitrogen mixed gas to form a graphitized carbon layer on the surface to obtain a medium- and low-temperature porous absorbing iron-based composite ceramic.
[0094] Example 3
[0095] S1, magnetic loss phase pretreatment, Fe-Co (32wt%) was placed in an argon-protected ball mill, 0.6wt% stearic acid was added as a dispersant, and ball milling was carried out for 3 hours (rotation speed 400r / min) to obtain an antioxidant-coated magnetic loss phase.
[0096] S2, dielectric loss phase dispersion, short carbon fiber (1wt%) + SiC (9wt%) was added to anhydrous ethanol and ultrasonically treated for 35 minutes (power 500W), and then 0.1wt% silane coupling agent (KH550) was added and stirred for 1 hour to form a uniform suspension.
[0097] S3, the pretreated magnetic loss phase, ceramic matrix powder (SiO2 (9 wt%) + Al2O3 (5 wt%)), and low-temperature glass powder (B-Na-Si-O glass (32.3 wt%)) were mixed in proportion and ball-milled for 4.2 hours (rotation speed 400 r / min) to obtain matrix mixed powder;
[0098] S4, mixing the dielectric loss phase suspension with the matrix mixed powder and the pore-forming agent (calcium carbonate (8 wt%) + rice husk ash microspheres (3 wt%)), and stirring to form a uniform slurry.
[0099] S5, freeze injection molding, the slurry is injected into a pre-cooled metal mold (-12°C), then cooled to -18°C and kept warm for 7 hours to form an ice crystal template inside the slurry; vacuum freeze drying for more than 30 hours (temperature, -45°C, pressure 60Pa) to remove ice crystals and part of the solvent to form a green body with a closed-pore structure.
[0100] S6, pre-sintering stage (debinding and pore structure fixation), the green body is placed in an electric furnace, heated to 460℃ at a rate of 1.3℃ / min, and kept at this temperature for 1.8 hours to decompose the pore-forming agent and binder and form a stable skeleton.
[0101] S7, the main sintering stage (ceramic densification and glass phase melting), the temperature is raised to 690 ° C (heating rate 2.3 ° C / min), and kept at this temperature for 0.6 hours to melt the low-temperature glass phase and achieve matrix densification with a certain strength.
[0102] S8, grinding and polishing the sintered porous ceramics with a water-based organic solution to form a certain shape and size, and then heat-treating (530°C) under a nitrogen mixed gas to form a graphitized carbon layer on the surface to obtain a medium- and low-temperature porous absorbing iron-based composite ceramic.
[0103] Example 4
[0104] S1, magnetic loss phase pretreatment, Fe-Co (36wt%) was placed in an argon-protected ball mill, 0.6wt% stearic acid was added as a dispersant, and ball milling was carried out for 2.8 hours (rotation speed 400r / min) to obtain an antioxidant-coated magnetic loss phase.
[0105] S2, dielectric loss phase dispersion, carbon fiber (3wt%) + SiC (10wt%) was added to anhydrous ethanol, ultrasonicated for 40 min (power 500W), and then 0.3wt% of silane coupling agent (KH550) was added and stirred for 1 hour to form a uniform suspension.
[0106] S3, mix the pretreated magnetic loss phase, ceramic matrix powder (Al2O3 (5wt%) + SiO2 (6wt%) + calcium silicate (2.1wt%)), and low-temperature glass powder (B-Na-Si-O glass (30wt%)) in proportion, ball mill for 5 hours (speed 400r / min) to obtain matrix mixed powder.
[0107] S4, mixing the dielectric loss phase suspension with the matrix mixed powder and the pore-forming agent (calcium carbonate (6 wt%) + starch ash microspheres (1 wt%)), and stirring to form a uniform slurry.
[0108] S5, freeze injection molding, the slurry is injected into a pre-cooled metal mold (-10℃), then cooled to -20℃ and kept warm for 6.5 hours to form an ice crystal template inside the slurry; then vacuum freeze drying is performed for more than 24 hours (temperature, -45℃, pressure 60Pa) to remove ice crystals and part of the solvent to form a green body with a closed-pore structure.
[0109] S6, pre-sintering stage (debinding and pore structure fixation), the green body is placed in an electric furnace, heated to 500 °C at 1.0 °C / min, and kept at this temperature for 3 hours to decompose the pore-forming agent and binder to form a stable skeleton.
[0110] S7, the main sintering stage (ceramic densification and glass phase melting), the temperature is raised to 660 ° C (heating rate 2.2 ° C / min), and kept at this temperature for 0.8 hours to melt the low-temperature glass phase and achieve matrix densification with a certain strength.
[0111] S8, grinding and polishing the sintered porous ceramics with a water-based organic solution to prepare them into a certain shape and size, and then heat-treating them (540°C) under a nitrogen mixed gas to form a graphitized carbon layer on the surface to obtain a medium- and low-temperature porous absorbing iron-based composite ceramic.
[0112] Example 5
[0113] S1, magnetic loss phase pretreatment, carbonyl iron powder (8 wt%) was placed in an argon-protected ball mill, 0.5 wt% stearic acid was added as a dispersant, and ball milling was performed for 3.5 hours (rotation speed 400 r / min) to obtain an antioxidant-coated magnetic loss phase.
[0114] S2, dielectric loss phase dispersion, short carbon fiber (2wt%) + SiC (28wt%) was added to anhydrous ethanol and ultrasonically treated for 30 minutes (power 500W), and then 0.5wt% silane coupling agent (KH550) was added and stirred for 1 hour to form a uniform suspension.
[0115] S3, mixing the pretreated magnetic loss phase, ceramic matrix powder (SiO2 (13 wt%) + calcium silicate (4 wt%)), and low-temperature glass powder (B-Na-Si-O glass (34 wt%)) in proportion, and ball milling for 5 hours (rotation speed 400 r / min) to obtain matrix mixed powder;
[0116] S4, mixing the dielectric loss phase suspension with the matrix mixed powder and the pore-forming agent (calcium carbonate (8 wt%) + rice husk ash microspheres (2 wt%)), and stirring to form a uniform slurry.
[0117] S5, freeze injection molding, the slurry is injected into a pre-cooled metal mold (-15℃), then cooled to -19℃ and kept warm for 8 hours to form an ice crystal template inside the slurry; then vacuum freeze drying is carried out for more than 48 hours (temperature, -55℃, pressure 50Pa) to remove ice crystals and part of the solvent to form a green body with a closed-pore structure.
[0118] S6, pre-sintering stage (debinding and pore structure fixation), the green body is placed in an electric furnace, heated to 500 °C at 1.0 °C / min, and kept at this temperature for 3 hours to decompose the pore-forming agent and binder to form a stable skeleton.
[0119] S7, the main sintering stage (ceramic densification and glass phase melting), the temperature is raised to 660 ° C (heating rate 2.0 ° C / min), and kept at this temperature for 0.5 hours to melt the low-temperature glass phase and achieve matrix densification with a certain strength.
[0120] S8, grinding and polishing the sintered porous ceramics with a water-based organic solution to prepare them into a certain shape and size, and then heat-treating them (550°C) under a nitrogen mixed gas to form a graphitized carbon layer on the surface to obtain a medium- and low-temperature porous absorbing iron-based composite ceramic.
[0121] like Figure 2 As shown in the figure, the reddish-brown surface of the prepared medium-low temperature porous absorbing iron-based composite ceramic is the product of partial oxidation of iron powder, and the surface presents a complex pore structure. The complex pores help the material absorb electromagnetic waves and reduce reflectivity. Figure 3 The picture shows the microstructure of the sample, which shows that the cross section of the product has a rich layered pore structure. Figure 4 The wave absorption performance curve of the wave absorbing ceramic of the present invention is shown in FIG. -10dB indicates that the electromagnetic wave absorption rate in this band is 90%, and -20dB indicates that the electromagnetic wave absorption rate in this band is 99%. Compared with low-temperature organic materials, it meets the product standards.
[0122] Samples prepared according to the five examples of the present invention were tested, and the performance parameters of each example are shown in Table 2. All five examples have effective absorption ranges of 8-18 GHz, with other performance indicators varying slightly. The absorption performance of each example is related to the raw material formulation. The reflectivity in the 8-10 GHz range is below -10 dB, indicating excellent absorption performance. Due to its porous structure, it maintains a certain compressive strength while maintaining a low density, which is beneficial for product applications.
[0123] Table 2
[0124] Example <![CDATA[Body density g / cm 3 > Effective absorption range GHz Minimum reflectivity Compressive strength MPa 1 0.33 8-18 -21.82dB@14.84GHz 2.72MPa 2 0.22 8-18 -22.66dB@15.60GHz 2.87MPa 3 0.26 8-18 -28.07dB@18GHz 3.13MPa 4 0.23 8-18 -33.49dB@15.51GHz 2.96MPa 5 0.42 8-18 -17.74dB@8.55GHz 3.75MPa
[0125] The present invention optimizes the low-temperature sintering process, preserving the activity of the magnetic loss phase. The iron-based composite ceramic with a gradient porous structure obtained by freeze injection molding can achieve broadband and efficient wave absorption. The magnetic-dielectric synergistic loss is enhanced, breaking through the limitations of a single mechanism. Starch or rice husk ash microspheres are used as degradable pore-forming agents to achieve a green process and a short process design. The mechanical properties and stability of the iron-based composite ceramic structure are improved, expanding the application scenarios and providing cost advantages.
[0126] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.
Claims
1. A medium and low temperature porous wave absorbing iron-based composite ceramic, characterized in that: The following raw materials are included in weight percentage: Wave absorbing functional phase 10-50wt%, ceramic matrix 20-40wt%, pore forming agent 5-15wt%, Dielectric loss phase 5-10wt%, stearic acid 0.5-1wt%, silane coupling agent 0.2-0.5wt%, 30-34.5wt% of the binder phase; wherein: The absorbing functional phase is a magnetic loss absorber with carbonyl iron powder or Fe-Co alloy as the core; the dielectric loss phase is silicon carbide nanowires, chopped carbon fibers or reduced graphene oxide; the ceramic matrix is Al2O3, SiO2 or calcium silicate; the bonding phase is low-temperature glass powder, which is a B2O3-Na2O-K2O-SiO2 system with a softening point of 600-750°C; and the pore-forming agent is calcium carbonate, starch and rice husk ash.
2. A method for preparing the medium-low temperature porous wave-absorbing iron-based composite ceramic according to claim 1, comprising the following steps: Step 1: Raw material processing The microwave-absorbing functional phase is placed in a ball milling jar protected by argon, stearic acid is added as a dispersant, and the microwave-absorbing functional phase coated with antioxidant is obtained after ball milling and dispersion. The dielectric loss phase is added to anhydrous ethanol, and after ultrasonic treatment, a silane coupling agent is added and stirred to form a uniform dielectric loss phase suspension; Step 2: Mix in steps The treated absorbing functional phase is mixed with a ceramic matrix and a binder phase, and the mixture is dispersed by ball milling to obtain a ceramic matrix mixed powder; Mixing the dielectric loss phase suspension with the ceramic matrix mixed powder and the pore-forming agent, and stirring to form a uniform slurry; Step 3: Freeze injection molding of porous structure The slurry is injected into a mold at a sub-zero temperature, and the temperature is further reduced and kept warm, so that an ice crystal template is formed inside the slurry; the pre-frozen slurry is taken out and vacuum freeze-dried to remove the ice crystals and part of the solvent to obtain a green body with a closed-cell structure; Step 4: Two-stage low-temperature sintering The green body is placed in an electric furnace, and the temperature is gradually raised to 400-500° C. for pre-sintering, and the temperature is kept to decompose the pore-forming agent to form a stable skeleton; Continue to gradually raise the temperature to 600-750℃ for main sintering, and then keep the temperature to melt the low-temperature glass phase to obtain porous ceramics; Step 5: Processing and surface modification The sintered porous ceramic is ground and polished with a water-based organic solution, and then heat-treated in a nitrogen mixed gas at a temperature of 500-550° C. to obtain the medium- and low-temperature porous wave-absorbing iron-based composite ceramic.
3. The preparation method according to claim 2, wherein In step 1, the absorbing functional phase uses: carbonyl iron powder with a particle size of 1-20 μm, Fe-Co alloy powder with a particle size of 2-20 μm, and Fe:Co = 7:3; the ball milling time is 2-4 hours, and the rotation speed is 400 r / min; the dielectric loss phase uses: silicon carbide nanowires with a diameter of 50-200 nm and an aspect ratio >50 or short-cut carbon fibers with a length of 50-200 μm; the ultrasonic treatment is 20 to 40 minutes, and the power is 500 W; and the stirring is 0.5 to 2.5 hours.
4. The preparation method according to claim 2, wherein In step 2, the particle size of the ceramic matrix is 0.5-50 μm; the low-temperature glass powder is a B2O3-Na2O-K2O-SiO2 system with a softening point of 600-750°C; the ball milling is performed for 3 to 6 hours at a rotation speed of 400 r / min; the pore-forming agent is calcium carbonate with a particle size of 0.5 to 10 μm; and the starch and rice husk ash microspheres have a particle size of 0.05-1 mm.
5. The preparation method according to claim 2, wherein In step 3, the mold pre-cooling temperature is -10 to -15°C; the temperature is further lowered to -15 to -25°C, and the heat preservation is performed for 5 to 10 hours; the vacuum freeze drying is performed for 24 to 48 hours, the temperature is -40 to -55°C, and the pressure is ≤60Pa.
6. The preparation method according to claim 2, wherein In step 4, the temperature rise curve of the pre-sintering is 1-2.5° C. / min, and the holding time is 1.5-3 hours; the temperature rise curve of the main sintering is 2-3° C. / min, and the re-holding time is 0.5-1.5 hours.
Citation Information
Cited By
Method for efficiently reducing and purifying carbonyl iron powder
CN121627063A